Development and evaluation of Panax notoginseng saponins contained in an in situ pH-triggered gelling system for sustained ocular posterior segment drug delivery. Issue 2 (December 2021) - Lu, Peng; Wang, Renxing; Xing, Yue; Gao, Yanquan; Zhang, Qingqing; Xing, Bin; Zhang, Ying; Yu, Changxiang; Cai, Xinfu; Shang, Qiang; Kebebe, Dereje; Pi, Jiaxin; et al.
Abstract : Supplemental Digital Content is available in the text Abstract: Objective: This study aimed to lay the foundation for the research on Panax notoginseng saponins (PNS) in pH-sensitive in situ gel and the development and improvement of related preparations. Methods: We used Carbopol ® 940, a commonly used pH-sensitive polymer, and the thickener hydroxypropyl methylcellulose (HPMC E4M) as an ophthalmic gel matrix to prepare an ophthalmic in situ gel of PNS. In addition, formula optimization was performed by assessing gelling capability with the results of in vitro release studies. In vitro (corneal permeation, rheological, and stability) and in vivo (ocular irritation and preliminary pharmacokinetics in the vitreous) studies were also performed. Results: The results demonstrated that the in situ gelling systems containing PNS showed a sustained release of the drug, making it an ideal ocular delivery system for improving posterior ocular bioavailability. Conclusions: This study lays the foundation for the research of PNS contained in an in situ pH-triggered gel as well as the development and improvement of related preparations. It concurrently traditional Chinese medicine with a contemporary in situ gelling approach to provide new directions for the treatment of posterior ocular diseases such as diabetic retinopathy.